From Stone to Cloth: Symbolic Interpretations of Kidal Temple Statues in Contemporary Batik Motifs - Yudhistya Ayu Kusumawati; Feny Puspitasari (Jurnal Bahasa Rupa, 2025)
Malang’s ancient temple statues embody deep symbolic meanings that reflect the region’s spiritual, historical, and cultural identity. However, in contemporary society, these artifacts often remain static relics with limited engagement from younger generations, creating a disconnect between cultural heritage and modern life. This research addresses the question of how the symbolic essence of temple statues can be preserved and reintroduced in forms relevant to today’s creative industries. The study aims to visually reconstruct and reinterpret the symbolic values of Kidal Temple statues into contemporary batik motifs, transforming them into living cultural expressions that can be worn, circulated, and appreciated in everyday contexts. The objectives are twofold: to develop batik designs that authentically represent the visual and symbolic richness of the statues, and to propose a model of cultural preservation through design innovation that bridges heritage and contemporary creative practices. The research adopts the design thinking method due to its iterative and human-centered approach, encompassing five stages: empathy, define, ideation, prototyping, and testing. Cultural insights are gathered through field observation and expert interviews, translated into visual elements, explored through motif development, and refined through feedback from artisans and users. The outcomes include a series of batik patterns that reinterpret Kidal Temple symbolism, contributing to heritage preservation, reinforcing local identity, and offering practical strategies for integrating cultural narratives into the creative economy.